2010
DOI: 10.1007/bf03262708
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of dispensing paediatric medicines with high sugar content by pharmacists in Barcelona

Abstract: It is very important to advise parents, pharmacists, paediatricians, and paediatric dentists about low-sweetener paediatric medicine alternatives to control the high content sucrose medicines. The aim should be to reduce the intake of over the counter medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…21 In a previous study, it was found that 94% of parents did not brush the teeth of their children after syrup use. 22 For this reason, considering the cariogenic and erosive potential of sweetened and acidic medicaments that are prescribed for children, parents must be informed about this issue for adequate oral clearance after each dose of the drug as the primary step. 9 Medical prescriptions must always be supervised by healthcare professionals, and if possible, cariogenic or sugar-free medicaments should be prescribed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In a previous study, it was found that 94% of parents did not brush the teeth of their children after syrup use. 22 For this reason, considering the cariogenic and erosive potential of sweetened and acidic medicaments that are prescribed for children, parents must be informed about this issue for adequate oral clearance after each dose of the drug as the primary step. 9 Medical prescriptions must always be supervised by healthcare professionals, and if possible, cariogenic or sugar-free medicaments should be prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…9 Medical prescriptions must always be supervised by healthcare professionals, and if possible, cariogenic or sugar-free medicaments should be prescribed. 15,22 However, it is considered that opinions based on the production of medicaments with low sugar content may be recommended to drug manufacturers.…”
Section: Discussionmentioning
confidence: 99%